2019
DOI: 10.1016/j.ijcha.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Optimize Heart Failure Care Program on clinical and patient outcomes – The pilot implementation in Vietnam

Abstract: Background The Ho-Chi-Minh-city Heart Institute in Vietnam took part in the Optimize Heart Failure (OHF) Care Program, designed to improve outcomes following heart failure (HF) hospitalization by increasing patient awareness and optimizing HF treatment. Methods HF patients hospitalized with left ventricular ejection-fraction (LVEF) <50% were included. Patients received guideline-recommended HF treatment and education. Clinical signs, treatments and outcomes were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…Their findings revealed that the readmission rate among these patients was not associated with either long length of stay or mortality. According to the findings of the current study, there was no significant correlation between readmission and the two indicators of mortality and LOS, which confirms the study results of Lingsma et al 21 Do et al 27 studied the effect of a heart failure care program on the outcomes of 257 patients in Vietnam. Their results revealed that the readmission rate 60 days after discharge was 12.5%, which is similar to the readmission rate within 90 days after discharge in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Their findings revealed that the readmission rate among these patients was not associated with either long length of stay or mortality. According to the findings of the current study, there was no significant correlation between readmission and the two indicators of mortality and LOS, which confirms the study results of Lingsma et al 21 Do et al 27 studied the effect of a heart failure care program on the outcomes of 257 patients in Vietnam. Their results revealed that the readmission rate 60 days after discharge was 12.5%, which is similar to the readmission rate within 90 days after discharge in the present study.…”
Section: Discussionsupporting
confidence: 89%
“… 5 6 Prevalence of HF in older people was 10%–12% and accounted for 15% of all hospital admissions in Vietnam, which represents a huge economic burden. 7 8 Although there have been advances in the treatment, HF still carries a poor prognosis with a 30-day readmission rate of 8% in Vietnam. 7 However, there is limited evidence on ADL impairment in older hospitalised patients with HF in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“… 7 8 Although there have been advances in the treatment, HF still carries a poor prognosis with a 30-day readmission rate of 8% in Vietnam. 7 However, there is limited evidence on ADL impairment in older hospitalised patients with HF in Vietnam. It is important to understand the prevalence of ADL impairment and its impact on outcomes in older patients with HF to help guide management of this complex disease to improve both quality of life and survivability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pharmacological and device-based treatment, rehabilitation programs play an important role to ensure treatment adherence and education in HF patients. In Vietnam, the Optimize Heart Failure (OHF) Care Program was established to improve outcomes following HF hospitalization by increasing patient awareness and optimizing HF treatment [11]. The program could be successfully implemented in Vietnam and resulted in high usage of guideline-recommended drug therapy.…”
Section: Heart Failurementioning
confidence: 99%